Political Islam and Democracy (American Journal of Islam and Society, 2008)
On 14 May 2008, the Center for the Study of Islam and Democracy (CSID)held its ninth annual conference, entitled “Political Islam and Democracy:What Do Islamists and Islamic Movements Want?” at the Marriot RenaissanceHotel. This event brought together a distinguished group of experts todiscuss the relationship between religion and democracy, the MuslimBrotherhood and democratic evolution, negotiating and implementingdemocracy in diverse contexts, and other related topics.The first session, which included Nelly Lahoud (professor of politicaltheory, Goucher College), Mark Gould (professor of sociology, HaverfordCollege), and Amr Hamzawy (senior associate, Carnegie Endowment for International Peace) raised such issues as dismissing the idea that Islam anddemocracy are mutually exclusive and discrediting the terrorists who havehijacked Islam and turned it into the very things it stands against: radicalism,closed-mindedness, intolerance, and violence. Gould discussed “Sovereigntyof God: Constitutional Processes in Islam and Christianity,” and Hamzawydelved into an analysis of the Brotherhood’s draft party platform ...